Web 2.0 Tool Recommendations for Teachers - Negreiros, Joao Garrott Marques; Lei, Weng Chi (International Journal of Innovation and Research in Educational Sciences, 2019)

Uptake and depuration kinetics of dicofol metabolite 4,4′-dichlorobenzophenone, in the edible Asiatic clam Meretrix meretrix - Ivorra, Lucia; Cruzeiro, Catarina; Chan, Shek Kiu; Tagulao, Karen Araño; Cardoso, Patricia G. (Chemosphere, 2019)
Uptake and depuration kinetics of 4,4′-dichlorobenzophenone (main metabolite of dicofol) in the edible clam Meretrix meretrix were evaluated through a mesocosm experiment. M. meretrix was exposed to different dicofol concentrations (environmental concentration, D1 = 50 ng/L; supra-environmental concentration, D2 = 500 ng/L) for 15 days, followed by the same depuration period. To accomplish this goal, an analytical method was successfully optimized for 4,4′-DCBP using QuEChERS as extraction method with a range of concentrations 0.3–76.8 ng/g ww quantified by gas chromatography coupled to tandem mass spectrometry. Our results demonstrated different kinetics of accumulation depending on the two dicofol treatments. For D1, the uptake kinetic was best fitted using a plateau followed by one phase association kinetic model, while for D2 a one phase association kinetic model suited better. Similar bioconcentration factors were obtained for both concentrations but only animals exposed to D2, showed 4,4′-DCBP levels above the limits of quantification after 24 h exposure. These animals also showed lower uptake rate (ku) than organisms exposed to D1. During the depuration period, only organisms exposed to D1 successfully depurated after 24 h. On the other hand, although animals exposed to D2 presented higher elimination factor, they did not reach the original levels after depuration. Moreover, values detected in these clams were higher than the Maximum Residue Level (10 ng/g) established by the European legislation. This indicates that longer periods of depuration time than the ones used in this study, may be needed in order to reach safe levels for human consumption. This work also demonstrated that studies on metabolite kinetics during uptake/depuration experiments, could be a new alternative to understand the impact and metabolism of pesticides in the marine environment.
1 citations (Crossref) [2022-11-10]
Keywords: Bivalves; GC-MS/MS; Organochlorine pesticides; QuEChERS bioconcentration; Seafood

THE INTERPLAY BETWEEN A CONFUCIAN-HERITAGE CULTURE AND TEACHERS' SENTIMENTS AND ATTITUDES TOWARDS INCLUSION IN MACAU - Correia, Ana; Forlin, Chris; Teixeira, Vitor Manuel dos Santos; Kuok, A. C. H.; Monteiro, Elisa (2019)
Macau Special Administration Region (Macau SAR) is in the process of revising legislation concerning special and inclusive education. While the institutional discourse revolves around establishing inclusive education, it is unclear as to how the proposed changes will enable or depress this from occurring. This research, therefore, examined teachers’ attitudes towards inclusion as an indication of how well the new legislation may be received. Specifically, it investigated the interplay between 508 teachers working in private schools in Macau, that identified themselves as being inclusive schools, and teachers’ sentiments and attitudes towards the acceptance of inclusion and the role that Confucian values might play in shaping these attitudes. Discussion focusses on four key outcomes that need to be addressed if a significant improvement in including all children in regular schools in Macau is to be achieved. These include the need (1) to clarify the concept of inclusion at government, school, and teacher levels as it currently has ambiguous meaning; (2) to provide teachers with more opportunities to have systematic contacts with students with SEN, as this is crucial to improving their sentiments and attitudes toward people with disability; (3) to provide professional learning about inclusive education with better partnerships between teacher education institutions and schools to bridge theory and practice; and (4) to review the hidden influence of the subtle levels of time-honoured Confucian beliefs in Macau, which are not manifest nor easily detected but possibly have a deep impact on day-to-day practices.
Publisher: Zenodo

The interplay between a Confucian-heritage culture and teachers’ sentiments and attitudes towards inclusion in Macao - Correia, Ana; Monteiro, Elisa; Kuok, Angus; Forlin, Christine; Teixeira, Vitor (European Journal of Special Education Research, 2019)

Ten Spatial Problems with myGeoffice© for Teaching Purposes - Negreiros, Joao; Diakite, Ansoumane (Open Journal of Social Sciences, 2019)
For a long time, Geography did not hold a specific mathematical approach for any interpretation of space and this was the key reason why Geography degrees covered a wide variety of subjects such as demography, geology or topography to fulfill its curriculum. Yet from the 90’s, Geography finally created its own research agenda to meet four vital questions of any true geographer: “Where is …?”, “Is there a general spatial pattern?”, “What are the anomalies?” and “Why do these phenomena pursue certain spatial distribution?” The present review article addresses ten different spatial (point, regression and event) issues for learning and teaching aim where statistics play a major background role on the outcomes of myGeoffice© free Web GIS platform. These include cluster analysis, geographically weighted regression (GWR), ordinary least squares (OLS) regression, path analysis, minimum spanning tree, linear regression, space-time clustering and point patterns, for instance. Although the technical viewpoint of the algorithms is not explained at fully, this review paper makes a rather strong emphasis on the result’s interpretation, their respective meaning and when these techniques should be applied in a learning/teaching context.
0 citations (Crossref) [2022-09-21] Number: 7 Publisher: Scientific Research Publishing

Surface sediment composition and distribution of hydrothermal derived elements at the Duanqiao-1 hydrothermal field, Southwest Indian Ridge - Dias, Ágata; Liao, Shili; Tao, Chunhui; Su, Xin; Yang, Zhen; Ni, Jianyu; Liang, Jin; Yang, Weifang; Liu, Jia; Li, Wei; Dong, Chuanwan (Marine Geology, 2019)
9 citations (Crossref) [2022-09-21]

Realizing the promises of replication studies in education - Morrison, Keith (Educational Research and Evaluation, 2019)
5 citations (Crossref) [2022-09-21]

Perceived efficacy of teachers in Macao and their alacrity to engage with inclusive education - Monteiro, Elisa; Kuok, A. C. H.; Correia, Ana; Forlin, Chris; Teixeira, Vitor (International Journal of Inclusive Education, 2019)
This paper reports findings of a mixed methods study examining private school teachers’ perceptions of efficacy in dealing with the challenges presented by inclusive education in Macao. This is highly pertinent after the Government invited consultation to propose changes to amendments of the Decree Law of 1996 concerning the education of students with Special Education Needs (SEN) which will likely see private schools being required to accept these students in the future. Within the context of teacher preparedness for inclusive education, the study found that a number of teachers felt that they were not at all prepared to teach students with SEN. Whilst some teachers suggested that they lacked skills and knowledge in teaching in inclusive classrooms, some felt overwhelmed with the challenges. The teachers proposed that they would need to know how to provide instructional adaptations and modifications to support students with SEN. Implications for continuous development of teacher training and education are discussed within the context of improving teacher efficacy and how private school teachers could better respond to the challenges of inclusive education in Macao.
9 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13603116.2018.1514762
Keywords: Inclusive education; Macao; teacher education; teacher efficacy

O papel da imprensa em língua portuguesa de Macau: a ética, a ideologia do proissionalismo e o Código Deontológico dos Jornalistas - Simões, José Manuel (Estudos em Jornalismo e Mídia, 2019)
In Macao, Special Autonomous Region of China, there are two professional codes of journalists: one by the Portuguese and English Press Association of Macao and the other by the Macao Journalists’ Association, and there is no regulator in the territory or anyone who administers the rules or sanctions the journalists activity. here’s also no cases of known or reported censorship. However, according to the latest human rights report for this small region of Asia, “the Government has taken steps to limit the coverage of unfavorable news”, admitting the practice of self-censorship by the media.

Motives of Traditional and Emerging Donors in Aid Giving: Comparative Study between China and France - Diakite, Ansoumane D.; Phillips, Jenny O. L. (Journal of Social and Political Sciences, 2019)
Since the beginning of bilateral aid giving in the aftermath of the Second World War, the motives for aid giving have changed from being purely political and humanitarian to a mix of different interests. While poverty reduction is frequently stated as the goal of aid giving, it is commonplace for donors to use aid to advance their national interests. The rise of new, emerging donors is creating discussion in both the political and academic fields of aid giving. Traditional or western donors see emerging donors, such as China’s efforts in aid-giving as seeking the natural resources of the recipient countries. This paper provides a historical analysis of the aid-giving motivations underlying an emerging donor, China, and a traditional donor, France. The motives for China’s and France’s aid giving to African countries, with special focus on Guinea, show a great number of similarities.
1 citations (Crossref) [2022-09-21]
Keywords: Aid Giving Motives; Emerging Donor; Traditional Donor; Poverty Reduction

Macao air quality forecast using statistical methods - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Ferreira, Francisco (International Journal of Environmental Impacts: Management, Mitigation and Recovery, 2019)
0 citations (Crossref) [2022-09-21]

Macao air quality forecast using statistical methods - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Gonçalves, David; Ferreira, Francisco (Air Quality, Atmosphere & Health, 2019)
The levels of air pollution in Macao often exceeded the levels recommended by WHO. In order for the population to take precautionary measures and avoid further health risks under high pollutant exposure, it is important to develop a reliable air quality forecast. Statistical models based on linear multiple regression (MR) and classification and regression trees (CART) analysis were developed successfully, for Macao, to predict the next day concentrations of NO2, PM10, PM2.5, and O3. All the developed models were statistically significantly valid with a 95% confidence level with high coefficients of determination (from 0.78 to 0.93) for all pollutants. The models utilized meteorological and air quality variables based on 5 years of historical data, from 2013 to 2017. Data from 2013 to 2016 were used to develop the statistical models and data from 2017 was used for validation purposes. A wide range of meteorological and air quality variables was identified, and only some were selected as significant independent variables. Meteorological variables were selected from an extensive list of variables, including geopotential height, relative humidity, atmospheric stability, and air temperature at different vertical levels. Air quality variables translate the resilience of the recent past concentrations of each pollutant and usually are maximum and/or the average of latest 24-h levels. The models were applied in forecasting the next day average daily concentrations for NO2 and PM and maximum hourly O3 levels for five air quality monitoring stations. The results are expected to be an operational air quality forecast for Macao.
24 citations (Crossref) [2022-09-21]
Keywords: Macao; NO2; O3; PM10; PM2.5; Particulate matter

Lead: An iOS Application to Help in the Construction of New Habits - de Aguiar, André Wescley Oliveira; Bezerra, Jagni Dasa Horta; Marques, João Alexandre Lobo; de Alexandria, Auzuir Ripardo (International Journal of Information and Electronics Engineering, 2019)

Is the Belt and Road Initiative in Africa Sustainable? - Nwachukwu, Francis C. (The Journal of the Macau Ricci Institute, 2019)
In 2000, the China-Africa relationship was further strengthened with the establishment of the Forum on China-Africa Cooperation (FOCAC). The FOCAC offers a platform for consultation and cooperation mechanisms aimed at deepening diplomatic, security, trade and investment relations between China and African countries. Later came the Belt and Road Initiative (BRI) in 2013, an international trade network initiated by China that connects the three continents of Asia, Europe and Africa. The BRI focuses on the following key areas: cultural exchange; policy coordination; facilities connectivity; trade and investment; and financial integration. The BRI shares development objectives similar to those of the United Nations’ Sustainable Development Goals (SDGs). In fact, the BRI implements part of the SDGs and provides a practical mechanism to strengthen the Sino-Africa relationship, which Africa can leverage to meet its Sustainable Goals. Africa is linked through the “Road” of the BRI plan and has received infrastructural projects funded by China to facilitate trade and integration of the national economies along the trading route. Through the establishment of Economic and Trade Zones which attracts investments from Chinese companies, and building infrastructures such as sea ports and railways, China through the BRI framework is helping Africa meet UN SGD Goal 9 concerning industry, innovation and infrastructure. A practical effect is that the BRI is helping African countries overcome the infrastructure gap, create jobs, acquire skills and promote integration between countries.

Influência da nova estrutura fiscal de impostos de Angola na gestão de escolas privadas do municipio do Lobito - Armando Carlos Hombo Nogueira; Luis Miguel Pacheco; Marcus Antonio Almeida Rodrigues (Revista Gestao em Analise, 2019)
0 citations (Crossref) [2022-09-21]

Evaluating Mathematical Models for Morphological Classification of the QRS Complex - Do Vale Madeiro, J.P.; Barreto, D.; Marques, J.A.L.; Salinet, J.L. (Computing in Cardiology, 2019)

Environmental characterization of 4,4′-dichlorobenzophenone in surface waters from Macao and Hong Kong coastal areas (Pearl River Delta) and its toxicity on two biological models: Artemia salina and Daphnia magna - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Tagulao, Karen; Cruzeiro, Catarina (Ecotoxicology and Environmental Safety, 2019)
8 citations (Crossref) [2022-11-10]

Conceptualizing the Second Education Circuit for China’s Doctoral Students in Asia - Ge, Yun; Ho, Kong Chong (International Journal of Chinese Education, 2019)
The quest to become research universities of international repute has led flagship universities in East and Southeast Asia to develop a new focus on attracting international doctoral students. This paper aims to understand Chinese doctoral students’ mobility in the immediate region and their education to work perceptions. The study draws from a sample of 301 doctoral students from China who were studying at five universities in Japan, South Korea, and Singapore. Analysis on students’ decision making and after-study pathways highlights the regional exchange in related areas. We argue that this regional mobility of doctoral students, characterized as the second education circuit, is facilitated by a higher education migration infrastructure with three interactively weaved dimensions: commercial, social, and regulatory. The research findings suggest the growing importance of Asia as a regional second circuit of doctoral training for students from China.
1 citations (Crossref) [2022-09-21]

College Students’ Attitudes Toward Counseling for Mental Health Issues in Two Developing Asian Countries - Kuok, A. C. H; Rashidnia, J (Spritual Psychology and Counseling, 2019)

Classroom management into learning: using phenomenography to analyse student teachers’ conceptions of classroom management - Correia, Ana Maria (Revista Portuguesa de Investigação Educacional, 2019)
Classroom management is a critical area in the curriculum of teacher education programs. Student teachers’ conceptions of the role of the teacher as a class leader are frequently backed by their intuition and experience as students and socio-cultural context rather than evidence-based. This paper examines the conceptions of classroom management held by a multicultural group of forty-four student teachers attending a teacher education program at a higher education institute in Macao. The study aims at understanding the patterns of variation expressed by student teachers regarding the purpose and relevance of the object of learning. It compares a) the patterns of variation in students’ views of classroom management, and b) the students’ learning progress based on the pre-and post-test. The phenomenographic approach was adopted as the conceptual framework. Participants handwritten transcripts from student teachers at the first and last sessions of the course are the primary type of data collection. The findings show that changes in student teachers’ understanding of the conceptions of classroom management occurred during the course. The initial preferences for disciplinary approaches to classroom leadership have given way to conceptions of promoting the integration of classroom management into learning. The participants expressed increasing adherence to classroom management systems targeting and providing behavioural and academic supports and interventions to children and adolescents with and without special needs.
Artwork Size: 257-280 Páginas Publisher: Revista Portuguesa de Investigação Educacional

Characterization of the Natural Soundscape of Zebrafish and Comparison with the Captive Noise Conditions - Lara, Rafael A.; Vasconcelos, Raquel O. (Zebrafish, 2019)
Zebrafish is a well-established model organism in hearing research. Although the acoustic environment is known to shape the structure and sensitivity of auditory systems, there is no information on the natural soundscape of this species. Moreover, zebrafish are typically reared in large-scale housing systems (HS), although their acoustic properties and potential effects on hearing remain unknown. We characterized the soundscape of both zebrafish natural habitats and laboratory captive conditions, and discussed possible impact on auditory sensitivity. Sound recordings were conducted in five distinct zebrafish habitats (Southwest India), from quieter stagnant environments with diverse biological/abiotic sounds to louder watercourses characterized by current and moving substrate sounds. Sound pressure level (SPL) varied between 98 and 126 dB re 1 μPa. Sound spectra presented most energy below 3000 Hz and quieter noise windows were found in the noisiest habitats matching the species best hearing range. Contrastingly, recordings from three zebrafish HS revealed higher SPL (122-143 dB) and most energy below 1000 Hz with more spectral peaks, which might cause significant auditory masking. This study establishes an important ground for future research on the adaptation of zebrafish auditory system to the natural soundscapes, and highlights the importance of controlling noise conditions in captivity.
16 citations (Crossref) [2022-09-21]
Keywords: Animals; Animals; Laboratory; Auditory Threshold; Batrachoidiformes; Ecosystem; Environment; Female; Hair Cells; Auditory; Hearing; Housing; Animal; India; Male; Neuronal Plasticity; Noise; Saccule and Utricle; Seasons; Sexual Behavior; Animal; Sound; Species Specificity; Vocalization; Animal; Zebrafish; ambient noise; hearing sensitivity; natural habitat; sound pressure level; soundscape

Automatic Cardiotocography Diagnostic System Based on Hilbert Transform and Adaptive Threshold Technique - Marques, J. A. Lobo; Cortez, P. C.; Madeiro, J. P. D. V.; Fong, S. J.; Schlindwein, F. S.; Albuquerque, V. H. C. D. (IEEE Access, 2019)
The visual analysis of cardiotocographic examinations is a very subjective process. The accurate detection and segmentation of the fetal heart rate (FHR) features and their correlation with the uterine contractions in time allow a better diagnostic and the possibility of anticipation of many problems related to fetal distress. This paper presents a computerized diagnostic aid system based on digital signal processing techniques to detect and segment changes in the FHR and the uterine tone signals automatically. After a pre-processing phase, the FHR baseline detection is calculated. An auxiliary signal called detection line is proposed to support the detection and segmentation processes. Then, the Hilbert transform is used with an adaptive threshold for identifying fiducial points on the fetal and maternal signals. For an antepartum (before labor) database, the positive predictivity value (PPV) is 96.80% for the FHR decelerations, and 96.18% for the FHR accelerations. For an intrapartum (during labor) database, the PPV found was 91.31% for the uterine contractions, 94.01% for the FHR decelerations, and 100% for the FHR accelerations. For the whole set of exams, PPV and SE were both 100% for the identification of FHR DIP II and prolonged decelerations.
13 citations (Crossref) [2022-09-21] Conference Name: IEEE Access
Keywords: Acceleration; Biomedical monitoring; Cardiography; Cardiotocography (CTG); Databases; FHR DIP II; FHR accelerations; FHR baseline detection; FHR decelerations; Fetal heart rate; Hilbert transform; Hilbert transforms; Monitoring; PPV; Transforms; accurate fetal heart rate feature detection; accurate fetal heart rate feature segmentation; adaptive threshold technique; antepartum database; automatic cardiotocography diagnostic system; auxiliary signal; cardiotocographic examinations; computerized diagnostic aid system; digital signal processing techniques; fetal distress; fetal heart rate (FHR); fetal signals; maternal signals; medical signal detection; medical signal processing; obstetrics; patient monitoring; positive predictivity value; preprocessing phase; segmentation processes; uterine contractions; uterine contractions (UC); uterine tone signals; visual analysis

Artificial selection for male winners in the Siamese fighting fish Betta splendens correlates with high female aggression - Ramos, A.; Gonçalves, D. (Frontiers in Zoology, 2019)
In Southeast Asia, males of the Siamese fighting fish Betta splendens have been selected across centuries for paired-staged fights. During the selection process, matched for size males fight in a small tank until the contest is resolved. Breeders discard losing batches and reproduce winner batches with the aim of increasing fight performance. We assessed the results of this long-term selection process by comparing under standard laboratory conditions male and female aggressive behaviour of one strain selected for staged fights (“fighters”) and one strain of wild-types. The aggressive response of adult fish was tested against their mirror image or a size-matched conspecific. Fighter males were more aggressive than wild-type males for all measured behaviours. Differences were not only quantitative but the pattern of fight display was also divergent. Fighter males had an overall higher swimming activity, performing frequent fast strikes in the direction of the intruder and displaying from a distance. Wild-type males were less active and exhibited aggressive displays mostly in close proximity to the stimuli. Females of the fighter strain, which are not used for fights, were also more aggressive than wild-type females. Aggressive behaviours were correlated across male and female fighter siblings, suggesting common genetic and physiological mechanisms to male and female aggression in this species. The study further shows that results were largely independent of the stimulus type, with the mirror test inducing similar and less variable responses than the live conspecific presentation. These results suggest that selection for male winners co-selected for high-frequency and metabolic demanding aggressive display in males and also enhanced female aggression, opening a wide range of testable hypothesis about the ultimate and proximate mechanisms of male and female aggression in B. splendens.
Keywords: Aggression; Artificial selection; Domestication; Mirror test; Sexual conflict

Análise multimodal de estratégias discursivas: debate sobre o “bailout” entre Hillary Clinton e Bernie Sanders - Rocha, Nuno (ElingUP : Revista eletrónica de Linguística dos Estudantes da Universidade do Porto, 2019)
Este trabalho consiste numa análise multimodal das estratégias discursivas de Bernie Sanders e Hillary Clinton num excerto de um debate sobre as benesses dadas pela senadora norte americana aos bancos no pós-crise económica global de 2008. Bernie Sanders e Hillary Clinton evidenciaram uma linguagem corporal diferente, tanto na posição de locutor como na de interlocutor. No entanto, mesmo utilizando estratégias de comunicação verbal e física diferentes, os gestos utilizados enquadram-se no campo dos gestos recorrentemente observados em figuras políticas em estudos feitos por outros autores. Reforça-se assim a ideia de que os gestos em questão são regularmente utilizados por figuras políticas.
Number: 2